Phenotypic Variation of Avocado Leaves (Persea americana Mill.) in Gorontalo Regency - Pembengo, Nur Fadhillah; Jannah, Magfirahtul; Baderan, Dewi Wahyuni K.; Kandowangko, Novri Youla (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Avocado is a horticultural crop with considerable phenotypic diversity, particularly in leaf morphology. This study aimed to provide initial documentation of leaf phenotypic diversity in local avocado accessions from Gorontalo Regency, Indonesia. A descriptive exploratory method was conducted in eight villages: Dumati, Modelidu, Dulamayo, Tridarma, Tinelo, Kayumerah, Hepuhulawa, and Kayubulan. Twenty-two avocado accessions were characterized using 12 leaf morphological traits based on the IPGRI Descriptors for Avocado (1995). Qualitative and quantitative data were analyzed descriptively. The results revealed substantial variation in most leaf traits, with leaf shape showing the highest qualitative diversity. Seven leaf shape categories were identified: oval, ovate, lanceolate, oblong-lanceolate, oblong, roundish, and narrowly obovate. Leaf blade length ranged from 11.42 ± 1.27 to 20.07 ± 1.79 cm, while leaf width ranged from 5.08 ± 0.69 to 10.97 ± 0.97 cm. Variations were also observed in leaf color, pubescence density, primary vein number, and leaf texture, indicating diverse phenotypes among accessions. These findings provide baseline information for avocado germplasm conservation, local cultivar identification, and parent selection in breeding programs. Further molecular studies are recommended to validate the genetic relationships underlying the observed morphological variation and improve germplasm characterization.